Analysis of fractional MHD convective flow with CTNs’ nanoparticles and radiative heat flux in human blood - Aleem, Maryam; Inc, Mustafa; Sarwar, Shahzad; Asjad, Muhammad Imran; Alsubaie, A. S. A. (Frontiers in Energy Research, 2022)
The aim of the paper is two fold. Firstly, to analyze and investigate free convective, unsteady, MHD blood flow with single and multi walled carbon nanotubes (S&MWCNT s) as nanoparticles. The blood flow has been taken across upright vertical plate, oscillating in its own plane and engrafted in porous medium with slip, radiation and porosity effects. Nanofluid consist of human blood as base fluid; SWCNT’s and MWCNT’s as nanoparticles. Secondly, to discuss the three different definitions of fractional derivatives; namely, Caputo (C), Caputo–Fabrizio (CF) and Atangana–Baleanu (ABC) to obtain the solutions of such proposed models by Adomian decomposition method. The impact of fractional and physical parameters on concentration, velocity and temperature of human blood in the presence of slip effect are studied and projected diagrammatically. The paper ends by providing some numerical results: impart the reliableness, efficiency, significant features and are simple in computation with eminent accuracy of process for non-Newtonian Casson nanofluid fractional order models. It is observed that velocity of fluid decreases with SWCNT’s & MWCNT’s volume fraction and increase in CNT’s volume fraction increases blood temperature which ultimately enhances heat transfer rates. The results acquired are in excellent correspondence with the exact results.